Handbook of Asian sovereign bond markets: yield & risk - Syed Mohamed, Mohamed Ariff; Cheng, Fan Fah; Ramadilli Mohd, Shamsher Mohamad (Universiti Putra Malaysia Press, 2013)
Excessive borrowings relative to the ability to service loans constitute sovereign debt crisis, and it is not limited only to developed countries. This book is on the pricing of sovereign debt in 17 bond markets across Asia: from Japan in the Far East and Israel in West Asia. The 17 markets include the very large bond market of Japan, which ranks equal among the largest five markets namely in the UK, the USA, Germany and Switzerland. Sovereign debt overhang is allegedly destabilizing the world economy from October 2011, since when the then Eurozone crisis transformed into government debt overhang crisis. This book is about the economics of how the sovereign debts are rated, priced and sold on the basis of perceived risk by investors buying and selling debt instruments. Developed economies' debt burden as a percentage of national income has risen over 25 years from about 40 percent of GDP to the current figure of about 80 percent largely as a result of profligate government spending. So governments are now overhung with loans.